Corneal edema after cataract surgery in diabetic and non-diabetic patients - Indrajati, Christina; Rahmawati, Atik; Mahardika, Nabila Ayu (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2024)
Patients with diabetes mellitus undergoing phacoemulsification cataract surgery face an elevated risk of corneal edema, primarily due to metabolic disturbances that impair endothelial cell function, leading to delayed post-operative recovery. This prospective cohort study aimed to examine the relationship between diabetes mellitus and the incidence of corneal edema following phacoemulsification. A total of 180 cataract patients scheduled for surgery at Sultan Agung Eye Center, Semarang, and Dr. R. Soedjati Soemodiardjo Regional Public Hospital, Purwodadi, Indonesia, between July and August 2023, were enrolled. Participants were divided into two groups based on the presence or absence of diabetes mellitus. Corneal edema and visual acuity were evaluated on post-operative days 1 and 7. Statistical analyses assessed the association between diabetes mellitus and post-operative corneal edema, with a significance threshold set at p < 0.05. The results indicated that pre-operative visual impairment was significantly worse in non-diabetic patients compared to diabetic patients (p = 0.000). However, post-operative visual improvement was significantly greater in non-diabetic patients on both day 1 (p = 0.02) and day 7 (p = 0.00) compared to diabetic patients. Additionally, the incidence of corneal edema was significantly higher among diabetic patients on both day 1 (p = 0.004) and day 7 (p = 0.001) post-surgery. These findings suggest that diabetes mellitus is associated with a higher risk of corneal edema and delayed visual recovery following phacoemulsification cataract surgery.